Formulation and Characterization of Solid Tablets Using Solid Dispersion Matrix Technology: A Systematic Literature Review - Intan Nurcahyani; M. Abdul Jabar; M. Raka Werdaya; Septanti, Risti; Satrio Adiputra; Nia Yuniarsih (HM Publisher, 2023)
The formulation of solid tablet preparations using solid dispersion matrix technology involves the selection of active ingredients, polymer matrices, fillers or enhancers, and lubricants. The active ingredient is the drug component that provides a therapeutic effect to the patient. This study aimed to conduct a systematic review study to explore the formulation and characterization of solid tablet dosage forms using solid dispersion matrix technology. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the formulation and characterization of solid tablet preparations using solid dispersion matrix technology. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Solid dispersion matrix technology is one of the approaches used in the formulation of pharmaceutical preparations, especially solid tablets, to achieve controlled and effective drug release. In this technology, the drug is dispersed homogeneously in a solid polymeric matrix, which acts as a binding agent. The basic principle of solid dispersion matrix technology is that the drug is delivered via gradual release from the polymer matrix.